Digital fast pulse shape and height analysis on cadmium–zinc–telluride arrays for high‐flux energy‐resolved X‐ray imaging. (14th December 2017) - Abbene, Leonardo; Principato, Fabio; Gerardi, Gaetano; Bettelli, Manuele; Seller, Paul; Veale, Matthew C.; Zambelli, Nicola; Benassi, Giacomo; Zappettini, Andrea
Abstract : This work presents the performance of a 2 mm‐thick CZT pixel detector, with pixel pitches of 500 and 250 µm coupled to a custom 16‐channel digital readout electronics, performing on‐line fast pulse shape and height analysis. Charge‐sharing investigations were performed, at both low and high fluxes, using fine time coincidence analysis and pulse shape analysis. Abstract : Cadmium–zinc–telluride (CZT) arrays with photon‐counting and energy‐resolving capabilities are widely proposed for next‐generation X‐ray imaging systems. This work presents the performance of a 2 mm‐thick CZT pixel detector, with pixel pitches of 500 and 250 µm, dc coupled to a fast and low‐noise ASIC (PIXIE ASIC), characterized only by the preamplifier stage. A custom 16‐channel digital readout electronics was used, able to digitize and process continuously the signals from each output ASIC channel. The digital system performs on‐line fast pulse shape and height analysis, with a low dead‐time and reasonable energy resolution at both low and high fluxes. The spectroscopic response of the system to photon energies below ( 109 Cd source) and above ( 241 Am source) the K ‐shell absorption energy of the CZT material was investigated, with particular attention to the mitigation of charge sharing and pile‐up. The detector allows high bias voltage operation (>5000 V cm −1 ) and good energy resolution at moderate cooling (3.5% and 5% FWHM at 59.5 keV for the 500 and 250 µm arrays, respectively) by using fast pulse shaping with a low dead‐time (300 ns). Charge‐sharing investigations were performed using a fine time coincidence analysis (TCA), with very short coincidence time windows up to 10 ns. For the 500 µm pitch array (250 µm pitch array), sharing percentages of 36% (52%) and 60% (82%) at 22.1 and 59.5 keV, respectively, were measured. The potential of the pulse shape analysis technique for charge‐sharing detection for corner/border pixels and at high rate conditions (250 kcps pixel −1 ), where the TCA fails, is also shown. Measurements demonstrated that significant amounts of charge are lost for interactions occurring in the volume of the inter‐pixel gap. This charge loss must be accounted for in the correction of shared events. These activities are within the framework of an international collaboration on the development of energy‐resolved photon‐counting systems for high‐flux energy‐resolved X‐ray imaging (1–140 keV).